The steady states of a non-cooperative model arising in reactor dynamics. (August 2016) - Chen, Ruipeng; Li, Xiaoya
Abstract: In this work, we investigate the existence and stability of coexistence states of a reaction–diffusion model originated by the theory of nuclear reactors. By converting it to an equivalent system with linear cooperative part, we obtain the necessary and sufficient conditions for the existence of coexistence states via lower and upper solutions method. In addition, stability results and a criterion are also given to enrich and complement those available in the literature.